The Effects of Government’s Role on Convergence Acceleration in Indonesia - Vania, Mia; Santoso, Dwi Budi (Journal of Development Economic and Social Studies, 2025)
This study aims to determine the influence of government roles through expenditures in education, health, and development sectors on the acceleration of convergence in Indonesia. The data used is panel data covering 33 provinces from 2010 to 2022. The method employed in this research is panel data regression with a convergence model. The variables used include education expenditure, health expenditure, and development expenditure. The results of the study indicate that the variables of education expenditure, health expenditure, and development expenditure have no effect on accelerating convergence. In addition, the three variables have no effect on economics growth.   Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh dari peran pemerintah melalui pengeluaran di bidang pendidikan, kesehatan, dan pembangunan terhadap percepatan konvergensi di Indonesia. Data yang digunakan merupakan data panel meliputi 33 provinsi dari tahun 2010-2022. Metode yang digunakan dalam penelitian ini merupakan regresi data panel model konvergensi. Variabel yang digunakan antara lain belanja pendidikan, kesehatan, dan pembangunan. Hasil dari penelitian menunjukkan variabel belanja pendidikan, belanja kesehatan, dan belanja pembangunan tidak berpengaruh terhadap percepatan konvergensi. Selain itu, ketiga variabel tersebut tidak berpengaruh terhadap pertumbuhan ekonomi.